Retrofit of floating storage and regasification units for ammonia and hydrogen: Material selection, thermal analysis, and boil-off gas utilization - Dindha Andriani (16444530) (2025)
The shift towards energy transition and decarbonization has raised interest in retrofitting Liquefied Natural Gas (LNG) Floating Storage and Regasification Units (FSRUs) for ammonia and hydrogen storage. This study uses Computational Fluid Dynamics (CFD) simulations to assess tank materials, insulation, heat ingress, and Boil-Off Gas (BOG) generation. The findings show that a stainless-steel ammonia tank results in a 0.02 % BOG rate by Day 5. For hydrogen, the BOG reduces from 1.66 % using Rigid Polyurethane Foam (RPF) to 0.4 % using 20 Multi-Layer Insulation (MLI) layers and a Vacuum Cooled Shield (VCS). It is estimated that 50 MLI layers are required to achieve a BOG rate below 0.01 %. Repurposing BOG through fuel cells generates 30.6 MWh from ammonia and 11.8 MWh from hydrogen. Considering tanks account for a major expense, the Benefit-Cost Ratio (BCR) was calculated to assess the financial impact of material selection and insulation for these tanks, showing that hydrogen storage tanks with 40 and 50 MLI layers acheived the highest BCRs of 1.152 and 1.161, repectively. Hence, this study comprehensively analyzes adapting ammonia and hydrogen to existing LNG infrastructure. Other Information Published in: International Journal of Hydrogen Energy License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ijhydene.2025.04.162